The Influence of Live Shopping and Word of Mouth Promotions on Purchasing Decisions which are Moderate by Price on Tiktok Shop Users (Case Study of The Originote Skincare Products in Pandeglang Regency) - Relin, Relin; Yunita, Irma; Permatasari, Novelia Kiki (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to analyze the effect of Live Shopping on purchasing decisions with price as a moderating variable, on skincare products the Originote in pandeglang district on purchasing tiktok Shop. Using quantitative methods with an associative approach, this study involved 140 respondents who were taken evenly from 35 sub-districts in Pandeglang Regency, with 4 samples from each sub-district. Data was collected through questionnaires and analyzed using the Partial Least Squares (PLS) method. The results showed that Live Shopping has a positive and significant effect on purchasing decisions, while Word of Mouth promotion has a positive but insignificant effect on purchasing decisions. In addition, price is proven to moderate negatively / weaken and positively / strengthen between Live Shopping and word of mouth promotion on purchasing decisions. these findings provide important information for digital marketing strategies, especially in the context of e-commerce and the use of social media platforms to increase sales.